Combustion, performance and emission analysis of a diesel engine fueled with methyl esters of Jatropha and fish oil with exhaust gas recirculation. (February 2019) - Kumar, M. Saravana; Prabhahar, M.; Sendilvelan, S.; Singh, Sanjay; Venkatesh, R.; Bhaskar, K.
Abstract: This research work is based on experiments conducted with 20% blend of Jatropha Oil Methyl Ester (JOME) and Fish Oil Methyl Ester (FOME) with diesel, on a compression ignition engine with and without Exhaust Gas Recirculation (EGR). At the rated power output, the brake thermal efficiency decreases from 28.43% to 27.12% for 20% JOME with 20% EGR compared to diesel and the specific energy consumption increases from 12, 936 to 13, 264 kJ/kWh, the unburned hydrocarbon varies from 0.7 g/kWh with diesel to 0.8 g/kWh for 20% JOME with EGR while the variation is from 0.7 to 0.9 g/kWh for 20% FOME compared to 0.7 g/kWh for diesel and also carbon monoxide emissions at rated power output from 16.75 g/kWh with diesel to 14.235 g/kWh with 20% JOME and 20% EGR. Lowest carbon monoxide emission achieves at 20% JOME blend with 10.32 g/kWh. At rated power output the oxides of nitrogen emissions vary from 7.45 g/kWh with diesel and 20% JOME without EGR to 4.8 g/kWh with 20% JOME with 20% EGR while they vary from 7.6 to 6.4 g/kWh for 20% FOME compared to 7.3 g/kWh for diesel.